2002
DOI: 10.1007/s005350200025
|View full text |Cite
|
Sign up to set email alerts
|

Tumor thrombi in the portal vein system originating from gastrointestinal tract cancer

Abstract: Intraluminal tumor thrombus in the portal vein (PV) system originating from gastrointestinal (GI) tract cancer is a rare condition. There are two types of such thrombi, one arising indirectly from metastatic liver cancer and the other directly from the primary lesion. We report here three patients with the direct type and two with the indirect type; i.e., a total of five patients with gastric or large intestinal cancer with PV tumor thrombus. In all patients, the primary lesion was surgically resected; in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 11 publications
1
42
0
Order By: Relevance
“…The general features are: (1) a distinct male preponderance (86.3%), (2) occurrence in the elderly (mean 63.7 years), (3) a large proportion of type II or III carcinoma (ulcerative type) (60.8%) located in the cardia or body (66.7%), (4) a high rate of poorly differentiated adenocarcinoma (75.0%), (5) a high rate of liver metastasis (52.1%), and (6) a high serum AFP concentration (63.6%). 27 However, the features of our patient did not accord with the general features of the disease. A review of the literature showed also that PTT tends to be located predominantly throughout the intra-and extrahepatic portal vein, although the description of location was not precise in most cases.…”
Section: Discussionmentioning
confidence: 64%
“…The general features are: (1) a distinct male preponderance (86.3%), (2) occurrence in the elderly (mean 63.7 years), (3) a large proportion of type II or III carcinoma (ulcerative type) (60.8%) located in the cardia or body (66.7%), (4) a high rate of poorly differentiated adenocarcinoma (75.0%), (5) a high rate of liver metastasis (52.1%), and (6) a high serum AFP concentration (63.6%). 27 However, the features of our patient did not accord with the general features of the disease. A review of the literature showed also that PTT tends to be located predominantly throughout the intra-and extrahepatic portal vein, although the description of location was not precise in most cases.…”
Section: Discussionmentioning
confidence: 64%
“…Only one case of acinar cell carcinoma has been reported so far [15] (Table 1). Although tumor thrombosis in the portal venous system is rarely recognized in patients with malignant tumors except for HCC, in addition to these pancreatic tumors, a few exceptional malignancies such as gastric cancer [16][17][18][19][20][21][22][23][24], colorectal cancer [4,23,[25][26][27][28][29][30][31], gallbladder cancer [32], renal cancer [33], malignant lymphoma [34][35][36], and malignant melanoma [37] have been reported to develop portal tumor thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Portal vein involvement by neoplasm is classified as either extrinsic portal vein occlusion or intraluminal tumor thrombus. The former is usually caused by pancreatic cancer, gallbladder cancer, and metastatic lymph nodes while the latter is usually caused by hepatocellular carcinoma and some alpha-feto protein-producing gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The former is usually caused by pancreatic cancer, gallbladder cancer, and metastatic lymph nodes while the latter is usually caused by hepatocellular carcinoma and some alpha-feto protein-producing gastric cancers. 6 In addition, acute portal vein thrombosis may also occur as a complication of post-ERCP pancreatitis in relation to internal drainage for malignant biliary obstruction. 8 In our case, metallic stents placed in the biliary tract may have contributed to portal vein obstruction and/or thrombosis.…”
Section: Discussionmentioning
confidence: 99%